Answer:
x = 7
x = 5
Step-by-step explanation:
[tex]\sqrt{x^2-4x-5}=2x-10[/tex]
We square both sides to get rid of the square root.
[tex](\sqrt{x^2-4x-5})^2=(2x-10)^2[/tex]
[tex]x^2-4x-5=(2x-10)^2[/tex]
We know (a + b)^2 = a^2 + 2ab + b^2 so now the right side becomes,
[tex]x^2-4x-5={(2x)^2-2(2x)(10)+(10)^2}\\[/tex]
[tex]x^2-4x-5=4x^2-40x+100\\[/tex]
Now move everything to the right side,
[tex]4x^2-x^2-40x+4x+100+5=0\\3x^2-36x+105=0\\[/tex]
Now we can take 3 common ,
[tex]3(x^2-12x+35)=0\\x^2-12x+35=0[/tex]
now this is a simple quadratic equation, we can use two methods.
1) Quadratic formula
2) Factorize
We use the factorizing method,
we need two numbers when multiplied give us +35 and when added give us -12 so the numbers are -7 and -5 because -7 x -5 = +35 and
- 7 - 5 = -12
[tex]x^2-7x-5x+35=0[/tex]
[tex]x(x-7)-5(x-7)=0\\(x-7)(x-5)=0\\x-7=0 \ \ \ , \ \ \ x-5=0\\x=7 \ \ \ \ \ \ \ \ , \ \ \ \ x=5[/tex]